Florida Insecticide, Miticide, and Nematicide Pricing and Expectations - Mark A. Mossler (EDIS)
PI-135, a 3-page fact sheet by M.A. Mossler, provides a table of costs per acre for pesticide active ingredients. Published by the UF/IFAS Pesticide Information Office, September 2006.